FAKTOR-FAKTOR PENDUKUNG KESEJAHTERAAN SUBJEKTIF PEKERJA - , Hartanti ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The objective of this research is to trace effect of the individual factor (intrinsic) including sense of humor, personality type of the big five personality, gratitude, and situational factors (extrinsic) consist of social support, work reward, and work condition of subjective well- being, finally it will be known the determinant factors of subjective well-being for the worker in the organization in Indonesia. Subjects were 139 workers and 56 supervisors in Y, Inc. Data collection used closed and opened questionnaire, observation, interview and focus group discussion. To understand differences between subjective well-being viewed from work level and sexe is used statistic analysis, regression analysis and t-test. Personality fit with the demands of work and organizational culture, will increase the subjective well-being. Strict rules on the company and the typical Javanese culture whose views on the importance of alignment, making agreeableness as predictors of subjective well-being of its production employees and the employees supervisor.The personality type of agreeableness, neuroticism, sense of humor and social support become determinant of high-low subjective well- being PT. Yâs labors with F=5.786, p<0.01. Supervisor, predictor of subjective well-being are personality type variable of openness to experience, agreeableness, gratitude and work reward. Results show that laborâs subjective well-being is higher than supervisor (t=7.779, p<0.01). For supervisor, work reward is tool for self actualization, those are, prestigious, autonomy, safety, and protect, while for labors, work reward is used to fulfill basic needs. This matter makes labors more satisfied easily with work reward that is gotten because the work opportunity is also more limited. This research shows, the subjective well-being was not different based on gender.